Relação do perímetro escrotal com a média de peso do grupo contemporâneo para estimação de um modelo de ajuste - Dal-Farra, Rossano André; Lobato, José Fernando Piva; Fries, Luiz Alberto [UNESP] (My University, 1998)
Measurements of scrotal circumference (SC) of 8934 young Nelore bulls, distributed on 346 contemporary groups (GC) from herds under tropical pasture conditions, were analyzed. The GC, with at least five animals each, were defined as: males born in the same farm and year, from the same management group and with post-weaning weight and SC collected on the same date. The aim was to study if nutritional effect, evaluated by GC average yearling adjusted weight (MPGC), after acting directly on weight and SC, was strong enough so as to change the curvilinear relationship between SC and weight. Data were divided in five sets according to MPGC values. Three models were compared: using a single prediction equation for all sets; using common linear and quadratic regressors but unique intercepts for each set; and using different prediction equations for each set. The more parsimonious model was adequate to fit SC in all sets. The analysis supports the practice of pre-correcting SC for weight, before knowing the MPGC (a proxy for nutritional level), using a single set of correction factors.
Relation of scrotal circumference with contemporary group average weight to develop an adjust model
Keywords: Heterogeneous regressors; Modifying agents/effects; Nested regressors; Ordinary polynomials; Animalia